In vitro and in vivo anti-inflammatory models demonstrate oligopeptides play a significant role in anti-inflammatory properties of white tea - Feng Zhao; Xiaojuan Wang; Hui Liu; Jiang Qian (Journal of Functional Foods, 2024)
White tea is a kind of tea abundant in oligopeptides. The study aims to reveal the potential association between white tea oligopeptides and anti-inflammatory ability. Crude oligopeptide extracts of two subtype white tea (named BaiMudan and ShouMei) were prepared by removing known active substances including pigments, polyphenols, caffeine, polysaccharides, and free amino acids. Four abundant oligopeptides (LCAY, LLLSKKL, EVFAG, and ECDSCG) were identified through high-resolution mass spectrometry sequencing, and synthesized for anti-inflammation evaluation. In vitro experiments showed, expect there was no effect of EVFAG on TNF-α, the rests oligopeptides were all good at inhibit NO, IL-6, and TNF-α. In vivo experiments indicated a notable decrease in neutrophils of zebrafish yolk sac. Specifically, performance of LCAY was particularly outstanding, with its anti-inflammatory effect at 250 μg·mL−1 could exceed 100 μM dexamethasone. The prominent significance of this study is that it confirms white tea oligopeptides have a good anti-inflammatory activity.